Designing User Experience Website for Culinary MSMEs Using Participatory Design Method - Julianti, Sukma; Siregar, Herbert; Anisyah, Ani; Rasim, Rasim (Brilliance: Research of Artificial Intelligence, 2024)
The advancement of digital technology serves as a pivotal driver of business transformation across various sectors, including Micro, Small, and Medium Enterprises (MSMEs). This technology provides innovative solutions to enhance operational efficiency, broaden market reach, and improve customer experiences. However, the adoption of digital technology remains inconsistent among MSMEs, as evidenced by the case of Baso Jewol Gandasari. This research aims to develop a dedicated website tailored to this MSME to facilitate digitalization, simplify order management, and expand market share. The study employs a User Experience (UX)-driven design methodology utilizing Participatory Design, which actively involves business owners and customers in the feedback collection process to ensure that the developed features align with user needs. The evaluation process was conducted using the User Experience Questionnaire (UEQ) and the System Usability Scale (SUS), engaging 30 respondents for UEQ and 29 respondents for SUS. The findings reveal UEQ scores of 2.33 for attractiveness, 2.40 for perspicuity, 2.30 for efficiency, 1.96 for dependability, 2.16 for stimulation, and 1.88 for novelty. Additionally, the average SUS score of 83 is categorized as “Excellent”, signifying a high level of user satisfaction with the website. This research makes a significant contribution by offering digitalization solutions for MSMEs, enhancing operational efficiency, and fostering positive user experiences. Future studies are recommended to incorporate additional features, such as marketing analytics and personalization, to comprehensively address the evolving needs of MSMEs.